Development of a mathematical model of a fault-tolerant invsubbytes converter in a polynomial system of residue classes - I. A. Kalmykov; I. A. Provornov (Современная наука и инновации)
The article is devoted to the issue of improving the fault tolerance of the InvSubBytes procedure of SPN converters. Describes the possibility of applying a corrective code in a polynomial system of residue classes as a tool for detecting and eliminating the consequences of failures in the operation of replacement blocks.